Application fruit tree hole storage brick fertilizer is beneficial to increase the nitrogen utilization of grape under subsurface drip irrigation - Yao, Dongdong; Yang, Jianli; Jia, Haifeng; Zhou, Yufan; Lv, Qi; Li, Xujiao; Zhang, Huanhuan; Fesobi, Phillip; Liu, Huaifeng; Zhao, Fengyun; Yu, Kun (Frontiers in Plant Science, 2023)
It is very important to promote plant growth and decrease the nitrogen leaching in soil, to improve nitrogen (N) utilization efficiency. In this experiment, we designed a new fertilization strategy, fruit tree hole storage brick (FTHSB) application under subsurface drip irrigation, to characterise the effects of FTHSB addition on N absorption and utilization in grapes. Three treatments were set in this study, including subsurface drip irrigation (CK) control, fruit tree hole storage brick A (T1) treatment, and fruit tree hole storage brick B (T2) treatment. Results showed that the pore number and size of FTHSB A were significantly higher than FTHSB B. Compared with CK, T1 and T2 treatments significantly increased the biomass of different organs of grape, N utilization and 15 N content in the roots, stems and leaves, along with more prominent promotion at T1 treatment. When the soil depth was 15-30 cm, the FTHSB application significantly increased the soil 15 N content. But when the soil depth was 30-45 cm, it reduced the soil 15 N content greatly. T1 and T2 treatments obviously increased the activities of nitrite reductase (NR) and glutamine synthetase (GS) in grape leaves, also the urease activity(UR) in 30 cm of soil. Our findings suggest that FTHSB promoted plant N utilization by reducing N loss in soil and increasing the enzyme activity related to nitrogen metabolism. In addition, this study showed that FTHSB A application was more effective than FTHSB B in improving nitrogen utilization in grapes.